2021
DOI: 10.1002/anie.202014609
|View full text |Cite
|
Sign up to set email alerts
|

The Smelling Principle of Vetiver Oil, Unveiled by Chemical Synthesis

Abstract: Vetiver oil, produced on a multiton‐scale from the roots of vetiver grass, is one of the finest and most popular perfumery materials, appearing in over a third of all fragrances. It is a complex mixture of hundreds of molecules and the specific odorant, responsible for its characteristic suave and sweet transparent, woody‐ambery smell, has remained a mystery until today. Herein, we prove by an eleven‐step chemical synthesis, employing a novel asymmetric organocatalytic Mukaiyama–Michael addition, that (+)‐2‐ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The key odorant, responsible for this characteristic smell—which is a mystery until today—could be shown only recenty. 2-Epi-ziza-6(13)-en-3-one was proven as the active smelling principle of vetiver oil by an eleven-step chemical synthesis, employing a novel asymmetric organocatalytic Mukaiyama-Michael addition [ 117 ]. Vetiver EO is further characterized by high solubility in alcohol, which improves its miscibility with other perfumery material.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key odorant, responsible for this characteristic smell—which is a mystery until today—could be shown only recenty. 2-Epi-ziza-6(13)-en-3-one was proven as the active smelling principle of vetiver oil by an eleven-step chemical synthesis, employing a novel asymmetric organocatalytic Mukaiyama-Michael addition [ 117 ]. Vetiver EO is further characterized by high solubility in alcohol, which improves its miscibility with other perfumery material.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Thus, it appears in over a third of all fragrances, added to various products such as perfumes, deodorants, lotions, soaps, cosmetics, etc. [ 110 , 113 , 117 ]. The US Food and Drug Administration (FDA) classified C. zizanioides root EO as GRAS (generally recognized as safe) and approved the oil for use as a food and flavor additive in alcoholic beverages, chewing gum, candies, dairy, and baked food products [ 118 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Vetiver has an earthy, smoky, woody scent and is found naturally in the root of the vetiver plant ( Chrysopogon zizanioides ). 450 There are many components to it including valerenol, and β-cadinene 451 and khuismol 100 . 452 Recently, Ouyang et al identified (+)-2- epi -ziza-6(13)en-3-one as the main component responsible for the smell, 450 but there is still debate over the principle component smells which means that as yet there is no biotechnological process for production of Vetiver.…”
Section: Fragrancementioning
confidence: 99%
“…450 There are many components to it including valerenol, and β-cadinene 451 and khuismol 100 . 452 Recently, Ouyang et al identified (+)-2- epi -ziza-6(13)en-3-one as the main component responsible for the smell, 450 but there is still debate over the principle component smells which means that as yet there is no biotechnological process for production of Vetiver. However, (+)-zizaene which is the immediate precursor of khuismol was produced in E. coli : the MVA pathway was overexpressed to enhance the FPP supply and multiple copies of zizaene synthase from Chrysopogon zizanioides were also expressed yielding 25 mg L −1 product.…”
Section: Fragrancementioning
confidence: 99%
“…Some terpenic ketones (ziza-6(13)-en-3-one, 2-epi-ziza-6(13)-en-3-one, β-vetivone, α-vetivone and khusimone) and alcohols (khusimol, ( E )-isovalencenol and zizaen-3α-ol) collectively contribute to the global fragrance of vetiver [ 7 ]. Among them, 2-epi-ziza-6(13)-en-3-one has recently been shown to be the key compound responsible for the woody-ambery note specific to vetiver EO [ 8 ]. In contrast, terpenic acids (such as zizanoic acid) impair EO quality and make it unsuitable for perfumery applications [ 9 ], similar to (–)-geosmin, which is potentially associated with the undesirable earthy tonality of vetiver EO [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%